Community Partnership Program for Elementary School Teachers in Sungai Kakap District to Developing Higher-Level Thinking Test Instruments - Yani T, Ahmad; Ningsih, Kurnia; Afandi, Afandi; Tenriawaru, Andi Besse; Panjaitan, Ruqiah Ganda Putri (STKIP Singkawang, 2023)
Improving the quality of education is inseparable from the application of assessments that can accurately measure the final results of a learning process so that accurate, careful and objective assessment instruments are needed. Based on the results of an analysis of a number of findings based on the results of in-depth discussions with elementary school teachers in Kakap District, the problems that arose related to the making of learning outcomes test instruments that have been tested for reliability, include there are still many elementary school teachers in Kakap District, District Kubu Raya has not carried out the procedures for making learning achievement test instruments, especially appropriate higher order thinking tests, and there are still many teachers who do not know about the existence of software that can be used to analyze the reliability of learning achievement tests. This community partnership program activity aims to enable elementary school teachers in Kakap District to develop high-level thinking test instruments using available software so as to encourage teacher competency improvement in making reliable learning outcomes test instruments. The mechanism for implementing community partnership program activities for teachers in partner schools is carried out in 4 (four) stages, namely the planning, action, observation and evaluation, and reflection stages. The training participants consisted of 30 elementary school teachers in Kakap District. The results showed that there was an increase in the cognitive level in making the HOTs question instrument before and after the PKM.